Rasch analysis of the UK Functional Assessment Measure in patients with complex disability after stroke - Oleg N. Medvedev; Lynne Turner-Stokes; Stephen Ashford; Richard J. (Medical Journals Sweden, 2018)
Objectives: To determine whether the UK Functional Assessment Measure (UK FIM+FAM) fits the Rasch model in stroke patients with complex disability and, if so, to derive a conversion table of Rasch-transformed interval level scores. Methods: The sample included a UK multicentre cohort of 1,318 patients admitted for specialist rehabilitation following a stroke. Rasch analysis was conducted for the 30-item scale including 3 domains of items measuring physical, communication and psychosocial functions. The fit of items to the Rasch model was examined using 3 different analytical approaches referred to as "pathways". Results: The best fit was achieved in the pathway where responses from motor, communication and psychosocial domains were summarized into 3 super-items and where some items were split because of differential item functioning (DIF) relative to left and right hemisphere location (χ2 (10) = 14.48, p = 0.15). Re-scoring of items showing disordered thresholds did not significantly improve the overall model fit. Conclusion: The UK FIM+FAM with domain super-items satisfies expectations of the unidimensional Rasch model without the need for re-scoring. A conversion table was produced to convert the total scale scores into interval-level data based on person estimates of the Rasch model. The clinical benefits of interval-transformed scores require further evaluation.